2013
DOI: 10.1037/a0031795
|View full text |Cite
|
Sign up to set email alerts
|

Studying aesthetics with the method of production: Effects of context and local symmetry.

Abstract: We investigated the role of local and global context on visual patterns produced by normal participants, examining the effects of both top-down context (framing) and bottom-up content (element-internal symmetry) in a computer-based experimental framework. In the first study, we allowed participants to generate rectangles of arbitrary proportions and found an effect of framing on width-to-height ratios of rectangles produced, demonstrating the importance of taking visual framing into account when discussing hun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…A particularly well-known example is the perception of attractiveness of human faces (Grammer and Thornhill, 1994 ). In simple geometrical (graphic) and ornamental patterns, symmetry was shown to have a high correlation with aesthetic judgements (Jacobsen and Höfel, 2002 ; Westphal-Fitch et al, 2013 ; Rampone et al, 2016 ; al Rifaie et al, 2017 ). However, the role of symmetry in photography and artworks seems less clear.…”
Section: Experimental Aesthetics: Investigation Of Specific Image mentioning
confidence: 99%
“…A particularly well-known example is the perception of attractiveness of human faces (Grammer and Thornhill, 1994 ). In simple geometrical (graphic) and ornamental patterns, symmetry was shown to have a high correlation with aesthetic judgements (Jacobsen and Höfel, 2002 ; Westphal-Fitch et al, 2013 ; Rampone et al, 2016 ; al Rifaie et al, 2017 ). However, the role of symmetry in photography and artworks seems less clear.…”
Section: Experimental Aesthetics: Investigation Of Specific Image mentioning
confidence: 99%
“…First, theoretical frameworks, such as Locher, Overbeeke, and Wensveen’s (2010) model of aesthetic interaction or Leder, Belke, Oeberst, and Augustin's (2004) model of art appreciation, place the whole process within a specific physical context, such as a laboratory, a gallery, and so on. Second, a number of laboratory studies have recently found that even verbal and semantic contextual framing influence psychological and neural processes involved in the appreciation of art (Gartus & Leder, 2014; Kirk, Skov, Hulme, Christensen, & Zeki, 2009; Noguchi & Murota, 2013; Swami, 2013; Westphal-Fitch, Oh, & Fitch, 2013). Third, even when the physical context and format in which artworks are presented does not greatly affect the way people value their pictorial features (such as complexity, symmetry, or balance) genuine artworks viewed in the museum are experienced as more interesting and pleasant than their reproductions (Locher, Smith, & Smith, 1999, 2001).…”
mentioning
confidence: 99%
“…Perkins (1932) also obtained a move toward greater symmetry and discovered that the changes were progressive: 50 days after the drawings were shown, close to half of the participants produced perfectly or nearly perfectly symmetrical drawings from memory. Contemporary research still finds an affinity for ordered, structured, and symmetrical patterns and has provided novel insights into this phenomenon (e.g., Locher & Nodine, 1987; Tyler, 2002; Westphal-Fitch, Oh, & Fitch, 2013).…”
Section: Searching For An Explanationmentioning
confidence: 99%